Of floral fortune: tinkering with the grain yield potential of cereal crops. Issue 5 (11th October 2019) - Sakuma, Shun; Schnurbusch, Thorsten
Summary: Enhancing the yield potential and stability of small‐grain cereals, such as wheat ( Triticum sp.), rice ( Oryza sativa ), and barley ( Hordeum vulgare ), is a priority for global food security. Over the last several decades, plant breeders have increased grain yield mainly by increasing the number of grains produced in each inflorescence. This trait is determined by the number of spikelets per spike and the number of fertile florets per spikelet. Recent genetic and genomic advances in cereal grass species have identified the molecular determinants of grain number and facilitated the exchange of information across genera. In this review, we focus on the genetic basis of inflorescence architecture in Triticeae crops, highlighting recent insights that have helped to improve grain yield by, for example, reducing the preprogrammed abortion of floral organs. The accumulating information on inflorescence development can be harnessed to enhance grain yield by comparative trait reconstruction and rational design to boost the yield potential of grain crops.